Materialism Predicts College Students' Entrepreneurial Intention: A Serial Mediation Model - Li, Yanbin; Zhang, Yue; Zhang, Feng (Frontiers in Psychology, 2022)
Entrepreneurship is perceived as a critical pillar for unemployment alleviation and economic growth, especially in the era of COVID-19, which highlights the importance of the entrepreneurial potential of college students. The current research focused on the role of personal values in the entrepreneurial process and investigated the relationship between materialism and entrepreneurial intention among college students. Few studies have been examined this relationship, and the underlying mechanisms were also not identified. From the perspective of personal value, we hypothesized that materialism could positively predict entrepreneurial intention. Moreover, based on McClelland’s theory of need for achievement and the theory of planned behavior, a serial mediation model, with achievement motivation and entrepreneurial attitude as the mediators, was proposed. We conducted a correlational study on a sample of 1002 Chinese university students to examine our hypotheses. They participated in an online survey and completed the measurement of entrepreneurial intention, entrepreneurial attitude, materialism, and achievement motivation. The hypothesized models were examined through mediation and moderated mediation bootstrapping procedures. The results showed that materialism positively predicted college students’ entrepreneurial intention, and this relationship was serially mediated through achievement motivation and entrepreneurial attitude. Materialism boosted college students’ achievement motivation, which in turn was associated with a more positive entrepreneurial attitude and subsequently stronger entrepreneurial intention. The present research is the first to empirically examine this association’s mechanism and establish a serial mediation involving achievement motivation and entrepreneurial attitude. For the theoretical contribution, the present research provides a more comprehensive picture of the role of personal values in entrepreneurship by complementing the effect of materialism. And regarding the practical implications, the present research implies the silver lining of materialism and points out a possible way to enhance college students’ entrepreneurial intention, i.e., entrepreneurial education could take advantage of the characteristics of materialism and transform the “harmful” value into socially beneficial entrepreneurial intentions through enhancing their achievement motivation and positive attitude toward entrepreneurship.